Direct synthesis of thickness-tunable MoS2 quantum dot thin layers: Optical, structural and electrical properties and their application to hydrogen evolution. (May 2017) - Vikraman, Dhanasekaran; Akbar, Kamran; Hussain, Sajjad; Yoo, Geonwook; Jang, Ji-Yun; Chun, Seung-Hyun; Jung, Jongwan; Park, Hui Joon
Abstract: We report a layer thickness-tunable direct synthesis growth method for bi- to few-layer crystalline molybdenum disulfide (MoS2 ) thin layers. For the first time, a facile, cost effective, and mass-scalable direct synthesis approach, based on a chemical bath deposition, is designed for quantum dot(QD)-based MoS2 layers using (NH4 )6 Mo7 O24 and thiourea (CH4 N2 S) as precursors. Using this process, the uniformity of large area thin layer can be retained, and the applicability to various substrates can provide great opportunities in the fabrication of various atomically thin layered structures. The structural and optical properties of the MoS2 QD layers are systematically investigated. Raman, AFM and TEM analyses confirm the formation of continuous and crystalline bi-, tri- and few-layered MoS2 . Their electrical properties are evaluated by bottom-gate FETs, and a field-effect mobility value of 1.06 cm 2 V −1 s −1 and a current on/off ratio in the order of 10 5 are obtained. Particularly, MoS2 prepared as a thin film consisting QD structures of grains shows novel electrocatalytic property. MoS2 QDs on Au/Si are proven to be excellent electrocatalysts for hydrogen evolution reaction, featured by Tafel slope (94 mV decade −1 ), exchange current density (1.91×10 -1 mA cm −2 ) and long-term durability for 20 h. Our approach opens new avenues for the design and synthesis of functional MoS2 layers for energy harvesting. Graphical abstract: Highlights: A layer thickness-tunable direct synthesis growth method for bi- to few-layer crystalline MoS2 thin layers is reported. This approach is applicable to various substrates. The structural and optical properties of the synthesized MoS2 layers are systematically investigated. The electrical properties of the synthesized MoS2 layers are evaluated by bottom-gate FETs. MoS2 QDs on Au/Si are proven to be excellent electrocatalysts for hydrogen evolution reaction.